2012
DOI: 10.1097/fjc.0b013e31823f888f
|View full text |Cite
|
Sign up to set email alerts
|

Qiliqiangxin Inhibits the Development of Cardiac Hypertrophy, Remodeling, and Dysfunction During 4 Weeks of Pressure Overload in Mice

Abstract: Qiliqiangxin (QL), a traditional Chinese medicine, has been used in the treatment of chronic heart failure. However, whether QL can benefit cardiac remodeling in the hypertensive state is unknown. We here examined the effects of QL on the development of cardiac hypertrophy through comparing those of losartan in C57BL/6 mice underlying transverse aorta constriction for 4 weeks. QL and losartan were administrated at 0.6 mg and 13.4 mg·kg·d, respectively. Cardiac hypertrophy, function, and remodeling were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 38 publications
1
54
1
Order By: Relevance
“…Statistical analyses indicated effects of tumor cell injection on TPS90 (p<.0001) and TR90 (p<0.05), and effects of Losartan treatment on TPS90 (p<.001) and TR90 (p<0.05). These data suggest that the effects of Losartan treatment on peak shortening and relengthening were independent of the tumor condition and could be related to the tendency of Losartan to cause hypertrophy [27, 28]. …”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses indicated effects of tumor cell injection on TPS90 (p<.0001) and TR90 (p<0.05), and effects of Losartan treatment on TPS90 (p<.001) and TR90 (p<0.05). These data suggest that the effects of Losartan treatment on peak shortening and relengthening were independent of the tumor condition and could be related to the tendency of Losartan to cause hypertrophy [27, 28]. …”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory and others have reported that QL can attenuate myocardial remodeling and improve cardiac function in rats with experimental myocardial infarction [20-22]. Several studies have mentioned the protective effect of QL on cardiac remodeling, which are associated with inflammation regulation, energy metabolism improvement, and angiogenesis enhancement [23-26], but its mechanism has not been thoroughly elucidated to date. Therefore, using a post-myocardial infarction heart failure model, the present study evaluated the influence of QL on the heart function, cardiac fibrosis, and the expression of TGF-β1, p-Smads, collagen I, TNF-α and IL-6 to further explore whether TGF-β1 and NF-κB pathways are involved in the protective effects of QL during cardiac remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…It also inhibited myocardial inflammation and the death of cardiomyocytes. On the other hand, it promoted cardiomyocyte proliferation, leading to improved cardiac remodeling and cardiac function [36]. Another study showed that qili-qiangxin improved both systolic and diastolic cardiac functions, and it downregulated the cardiac chymase signaling pathway and chymase-mediated angiotensin II production in hypertensive rats [37].…”
Section: Qili-qiangxin Capsulesmentioning
confidence: 99%